Study protocol for development and validation of a framework to promote preparedness for caregiving in family caregivers of stroke survivors - Makhtar, Aniawanis; Syed Elias, Sharifah Munirah; Ahmad, Norfadzilah; Ab Ghani, Nor Nadiya; Suut, Norliza (IIUM Press, 2025)
Background: Caring for stroke survivors is a major challenge for many family caregivers in Malaysia who are inadequately prepared for their caregiving responsibilities, particularly during the critical transition from hospital to home. This lack of preparedness often leads to increased stress and burden, which negatively impacts the health and well-being of both the caregivers and stroke survivors. Thus, there is an urgent need to develop a framework to improve family caregiver preparedness in the Malaysian context. The purpose of this study is to develop and validate a framework to promote preparedness for caregiving among family caregivers of stroke survivors. Methods: This study will be conducted in four phases: a literature review, a quantitative study phase, a framework development phase, and a validation phase. A framework will be developed based on the results of the literature review and the quantitative study. The framework will be validated to ensure its relevance, completeness, and applicability. Conclusion: The framework will be culturally appropriate and sensitive to the needs of Malaysian family caregivers. It will equip family caregivers with knowledge about the needs of stroke survivors, as well as strategies to manage stress and prevent burnout, ultimately improving caregiving outcomes and the quality of life for both family caregivers and stroke survivors